Solvable constraints and unsolvable limits to global climate adaptation in coastal Indigenous food security - Eranga K. Galappaththi; Sithuni M. Jayasekara; Chrishma D. Perera; Gayanthi A. Ilangarathna; Hannah Garbutt (Cambridge Prisms: Coastal Futures)
Coastal systems are a major source of food for Indigenous communities. Climate change poses a high risk to coastal communities’ food security. Successful climate change adaptation practices are essential to ensure food security among Indigenous peoples. Yet, limits and constraints challenge climate change adaptation practices. Our study seeks to identify these limits and constraints in the context of food security among coastal Indigenous peoples. We performed a global scale systematic literature review using 155 scholarly articles to examine the constraints and limits to climate adaptation in the coastal food security and Indigenous peoples’ context. The three research questions are as follows: (i) What are the key constraints? (ii) What are the limits? (iii) What are the ways of overcoming the constraints? First, we found that, globally, the main constraints to adapting to climate change in coastal food security settings are related to governance, institutions and policies. Second, most limits are soft, to be solved, compared to hard limits on coastal systems. Third, we unveiled ways of overcoming the constraints, such as restoring coastal food system resilience, improving food accessibility and building the adaptive capacity of Indigenous peoples. The findings of the study provide valuable insights for policymakers, researchers and other relevant stakeholders involved in decision-making regarding coastal food security in the climate change adaptation context.